2022
DOI: 10.24996/ijs.2022.63.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Tigris River Water Quality on the Rotifers Community in Northern Baghdad by using the Canadian Water Quality Index (CCME-WQI)

Abstract: The water quality index was used for the evaluation of the quality of water, as well its impacts on the rotifer abundance, in the Tigris River as it passes through Mishahda City, northern Baghdad. Five sites were selected and samples were collected during October 2019 to September 2020. It was noticed that the index values in most sites have exceeded the upper limits of river waters. The values ranged from 40 (Poor) to 45 (Marginal) in all sites. While, the values were from 42 (Poor) to 65 (Fair) during differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thus, the index changed from fair in winter to marginal in summer, also discharging hightemperature water decreased DO and pH values into the river. Also, [35] explained that the values of this index fluctuated between 56 (marginal) to 69 (fair) near Al-Mishahda Town north of Baghdad related to the Anthropogenic effects. However, our findings disagree with, [36] finding that the water quality of the Tharthar-Tigris Canal lies within a poor grade.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, the index changed from fair in winter to marginal in summer, also discharging hightemperature water decreased DO and pH values into the river. Also, [35] explained that the values of this index fluctuated between 56 (marginal) to 69 (fair) near Al-Mishahda Town north of Baghdad related to the Anthropogenic effects. However, our findings disagree with, [36] finding that the water quality of the Tharthar-Tigris Canal lies within a poor grade.…”
Section: Resultsmentioning
confidence: 98%
“…Also, Abed et al [40] found that inverse relationship between TDS concentrations and Rotifera density in Tigris River northern Baghdad City.…”
Section: Salinitymentioning
confidence: 96%
“…Usually, conductivity for fresh water less than 325 μS cm -1 , between 325-975 μS cm -1 is called marginal, brackish between 975-3.250 μS cm -1 and saline more than 3.250 μS cm -1 [33]. Abed et al [40] showed that Rotifer density in Tigris River decreased with the increasing of BOD5 levels, related that to dumping of domestic sewage directly into the river.…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 99%
“…Another research was conducted by Ewaid and Abed to establish a mathematical Water Quality Index to measure the water quality of the Al-Gharraf River [10]. The Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI) was used to evaluate the water quality of the Al-Gharraf River for aquatic life protection and irrigation [11]. Al-Abadi studied the possibility of utilizing three distinct data-driven approaches to simulate stage-discharge relationship at Gharraf River system, these approaches are multilayer perceptron with backpropagation artificial neural network (MLP), M5 decision tree model, and Takagi-Sugeno (TS) inference system [12].…”
Section: Introductionmentioning
confidence: 99%